2017
DOI: 10.18203/2349-3291.ijcp20172704
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pneumonia with empyema at birth; a rare presentation

Abstract: Empyema thoracis is a rare complication of congenital pneumonia in neonates. Case characteristics: A newborn presented with severe respiratory distress had empyema thoracis. Outcome: patient was managed with chest tube insertion and antibiotics. Message: empyema can be a rare complication of congenital pneumonia and along with appropriate antibiotics, chest tube drainage is required for successful management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…2,6 Other studies have reported negative bacterial yield in the pleural fluid microscopy. 1,13,14 This perhaps may be due to small sample volume, unsatisfactory conditions of transport and storage which may impair pathogen viability, prior use or abuse of antibiotics and/or the method of culture that was done. The BACTEC culture system was used for the pleural fluid culture of our patient, as this has been found to have a higher yield probability with a shortened average turn-around time compared to the conventional method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Other studies have reported negative bacterial yield in the pleural fluid microscopy. 1,13,14 This perhaps may be due to small sample volume, unsatisfactory conditions of transport and storage which may impair pathogen viability, prior use or abuse of antibiotics and/or the method of culture that was done. The BACTEC culture system was used for the pleural fluid culture of our patient, as this has been found to have a higher yield probability with a shortened average turn-around time compared to the conventional method.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although there are no standard treatment protocol for neonatal ET yet, most of the previous reports like ours used antibiotics and chest tube drainage as treatment modalities with good outcomes. 1,3,6,13,14 Controversies still exist as to the duration of antibiotic use, however most clinicians advocate for an average of 3-6 weeks of antibiotics, with the intravenous route recommended in the early stages for enhanced pleural penetration. 3,18 Some other modalities advocated for treatment includes intra-pleural fibrinolytic treatment, video assisted thoracoscopic surgery and thoracotomy decortication.…”
Section: Discussionmentioning
confidence: 99%